Characterization of DMI, QoI and SDHI fungicides sensitivity of Ramularia collo‑cygni isolates in Argentina - Erreguerena, Ignacio Antonio; Havis, Neil David; Heick, Thies Marten; Gorniak, Kalina; Quiroz, Facundo Jose; Carmona, Marcelo Anibal (Springer, 2022)
Ramularia leaf spot (RLS) caused by the fungus Ramularia collo-cygni (Rcc) has become a threat to barley production in Argentina. All barley varieties are susceptible to RLS; thus, disease management relies on fungicides like quinone-outside inhibitors (QoIs), demethylation inhibitors (DMIs) and succinate dehydrogenase inhibitors (SDHIs). Europe reported Rcc resistance to fungicides associated with mutations in the fungicide's target genes. The aim of this work was to assess the impact of mutations on sensitivity levels in isolates of Rcc to QoIs, DMIs, SDHIs and a multi-site fungicide used for RLS control in Argentina and others countries. Twenty-one Rcc isolates were collected in the Buenos Aires province in the years 2012, 2015 and 2017 and tested against azoxystrobin (QoI), epoxiconazole and prothioconazole-desthio (DMIs), isopyrazam and fluxapyroxad (SDHIs) and chlorothalonil. For EC50 determination, a sensitivity assay was performed and cytb, cyp51 and sdh genes were sequenced for mutation analyses. All isolates showed G143A mutation that confers total resistance to QoIs (EC50 > 1 mg L−1). Three mutations in the target genes of DMIs (Y403C/S, G404D) were observed. Isolates with both amino-exchanges showed an increase in the EC50 towards DMIs. Mutations B-H266L and C-N87S in the target genes of SDHIs were detected, and both were related to a sensitivity reduction. Mutations occurrence tended to increase from 2012 to 2017 along with higher EC50 values. We found six haplotypes showing that Rcc is potentially adapting to fungicides in Argentina. Efforts must focus on new active ingredients and resistant varieties for a less fungicide-dependent agriculture based on IPM strategies.